Monitoring inflammation and airway remodeling by fluorescence molecular tomography in a chronic asthma model. Issue 1 (December 2015) - Stellari, Fabio; Sala, Angelo; Ruscitti, Francesca; Carnini, Chiara; Mirandola, Prisco; Vitale, Marco; Civelli, Maurizio; Villetti, Gino
Abstract Background Asthma is a multifactorial disease for which a variety of mouse models have been developed. A major drawback of these models is represented by the transient nature of the airway pathology peaking 24–72 h after challenge and resolving in 1–2 weeks. We characterized the temporal evolution of pulmonary inflammation and tissue remodeling in a recently described mouse model of chronic asthma (8 week treatment with 3 allergens: Dust mite, Ragweed, and Aspergillus; DRA). Methods We studied the DRA model taking advantage of fluorescence molecular tomography (FMT) imaging using near-infrared probes to non-invasively evaluate lung inflammation and airway remodeling. At 4, 6, 8 or 11 weeks, cathepsin- and metalloproteinase-dependent fluorescence was evaluated in vivo. A subgroup of animals, after 4 weeks of DRA, was treated with Budesonide (100 µg/kg intranasally) daily for 4 weeks. Results Cathepsin-dependent fluorescence in DRA-sensitized mice resulted significantly increased at 6 and 8 weeks, and was markedly inhibited by budesonide. This fluorescent signal well correlated with ex vivo analysis such as bronchoalveolar lavage eosinophils and pulmonary inflammatory cell infiltration. Metalloproteinase-dependent fluorescence was significantly increased at 8 and 11 weeks, nicely correlated with collagen deposition, as evaluated histologically by Masson's Trichrome staining, and airway epithelium hypertrophy, and was only partly inhibited by budesonide. Conclusions FMT proved suitable for longitudinal studies to evaluate asthma progression, showing that cathepsin activity could be used to monitor inflammatory cell infiltration while metalloproteinase activity parallels airway remodeling, allowing the determination of steroid treatment efficacy in a chronic asthma model in mice.